Restriction of liberty within the system of punishments - Margaryan, Anna; Arakelyan , Anahit (Bulletin of Yerevan University C: Jurisprudence, 2025)
Within the framework of the present article, two core aspects pertaining to the legal nature of the punishment known as restriction of liberty have been subjected to analysis. The first aspect focuses on the classification of this measure, aiming to determine whether it should be considered a form of punishment or a distinct instrument of criminal-legal influence. The second line of inquiry seeks to examine the legal essence of this type of punishment in light of the European Convention on Protection of Human Rights and Fundamental Freedoms.Simultaneously, the study raises the issue concerning the definition of the term "restriction of liberty" and highlights certain legislative challenges associated with the application of such restrictive measures.As a result of the analysis - encompassing the aims attributed to both punishments and security measures, as well as the ideological foundations underlying the implementation of liberty-restricting sanctions - it is concluded that restriction of liberty may be legitimately classified as a form of punishment under criminal law. At the same time, we concluded that, within the context of the European Convention, the restriction of liberty as a punishment, in most cases, may be considered as a measure that does not amount to a deprivation of personal liberty, nevertheless, in certain cases, it is impossible to deny the hybrid nature of this type of punishment.
Keywords: Restriction of liberty; criminal-legal influence measures; aims of punishment; personal liberty; right to freedom of movement; punishment related to deprivation of liberty; security measures; punishment legal nature